Gaya kepemimpinan, Empati dan Budaya Organisasi: Pilar Strategis dalam Meningkatkan Kinerja Pegawai PT. SNY - Fauzan, Muhammad Oceano; Zahiroh, Mun Yan; Setyawan, Suprihono; Rahayuningrat, Prahita Sri (Ekonomis: Journal of Economics and Business, 2025)
The purpose of this study was to determine the influence of leadership style, empathy, and organizational culture in improving employee performance at PT. SNY Balikpapan. This study used a quantitative approach by distributing questionnaires to 60 respondents who were both the population and the sample. Data analysis used multiple linear regression. The results showed that simultaneously there was a significant influence between the variables of leadership style, empathy, and organizational culture on performance. However, partially only the leadership style variable had a negative influence on employee performance at PT. SNY Balikpapan.